"Operating in the dark": Nurses' attempts to help patients and families manage the transition from oncology to comfort care. Issue 21 (9th August 2018) - Canzona, Mollie Rose; Love, Deborah; Barrett, Rolland; Henley, Joanne; Bridges, Sara; Koontz, Adam; Nelson, Sharon; Daya, Serena
Abstract: Aims and objectives: To investigate challenges nurses face when providing care for oncology patients transitioning from curative to palliative care and to identify educational and support opportunities for nurses. Background: Communicating with oncology patients/families transitioning from curative treatments to care focused on comfort can be problematic for a variety of reasons. Research suggests discrepancies exist between physicians' and patients' perceptions of probable length of life. These disconnects can deepen suffering. Oncology and palliative care nurses are well positioned to facilitate this transition. However, they receive little formal instruction regarding these complex scenarios beyond what occurs through on‐the‐job training. Methods: Twenty‐eight nurses working in oncology ( n = 14) and palliative care ( n = 14) settings participated. The constant comparative method was used to analyse the data. Results: Four themes emerged that characterise oncology and palliative care nurses' experiences: (a) coping with interprofessional communication errors during the transition, (b) responding to patient/family reactions to miscommunication about the goals of care, (c) navigating emotional connection to patients, and (d) adapting to sociocultural factors that influence information exchange. Conclusions: This study supports previous research regarding challenges related to patient reactions, family relationships and emotional burden during end‐of‐life care. However, it adds to the literature by a providing a more in‐depth explication of interprofessional and patient–physician communication barriers that negatively impact care. Relevance to clinical practice: Misunderstandings between patients, physicians and nurses have the potential to distress complicate nurses' efforts to support patients and families. Nurses reported a problematic power dynamic that impedes their ability to facilitate communication between patient and physician or to offer insights that could enhance patient care. Medical education and continuing education initiatives are needed to build understanding across professional roles and specialties and to improve comfort discussing worsening prognosis and end‐of‐life issues.